2016
DOI: 10.13080/z-a.2016.103.045
|View full text |Cite
|
Sign up to set email alerts
|

The influence of composts on yield and chemical elements of winter wheat and spring barley

Abstract: In 2013-2014, research was carried out on a Bathihypogleyi-Haplic Luvisol (LVh-gld-w) soil with predominant sandy loam and pH KCl 4.9-5.2 with a view to finding out how composts produced from sewage sludge, green waste and biogas production waste influenced grain and straw yields of winter wheat grown in the first year after compost incorporation and spring barley grown in the second year after incorporation as well as the concentrations of nitrogen, potassium and heavy metals in grain and straw. The field exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Together with the composts of all investigated types we incorporated 170 kg ha -1 of nitrogen (N) into soil, therefore, different amounts of composts were applied: 16.1 t ha -1 of sewage sludge, 23.0 t ha -1 of biogas production waste, 31.2 t ha -1 of green waste compost and 45.3 t ha -1 of manure compost. The influence of the composts used on the yield and quality of the first two plants in the crop rotation (winter wheat and spring barley) was described in this journal previously (Staugaitis et al, 2016), and for the purposes of this article, we discuss their influence on potatoes and the spring oilseed rape grown after the potato crop following the second compost incorporation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the composts of all investigated types we incorporated 170 kg ha -1 of nitrogen (N) into soil, therefore, different amounts of composts were applied: 16.1 t ha -1 of sewage sludge, 23.0 t ha -1 of biogas production waste, 31.2 t ha -1 of green waste compost and 45.3 t ha -1 of manure compost. The influence of the composts used on the yield and quality of the first two plants in the crop rotation (winter wheat and spring barley) was described in this journal previously (Staugaitis et al, 2016), and for the purposes of this article, we discuss their influence on potatoes and the spring oilseed rape grown after the potato crop following the second compost incorporation.…”
Section: Methodsmentioning
confidence: 99%
“…The first ten-day period of September was excessive in rainfall, the second and third ten day periods were close to optimal, consequently, these summer months were unfavourable for potato growth and tuber development. (Elmininkai Meteorological Station, 2015-2016 In the beginning of May 2016, a moderate drought occurred after spring oilseed rape sowing; however, during the second ten-day period of May the weather was close to optimal irrigation and the third period was a very heavy drought, thus spring oilseed rape tillering was poor. In June, a moderate drought occurred (HTC = 0.64); however, the rest of the spring oilseed rape growth period was abundant in rainfall.…”
Section: Methodsmentioning
confidence: 99%
“…Komposto gamybos metu susidaro naujas produktas, turintis augalams ir dirvožemiui reikalingų maistinių medžiagų, mikro-ir makroelementų bei organinės medžiagos (Compost production and use in the EU, 2007). Kompostas vertinamas kaip kompleksinė medžiaga, turinti gana įvairią ir kintančią sudėtį, kuri priklauso nuo pradinės komposto žaliavos (prieš mikroorganizmų veiklos pradžią) ir komposto gamybos proceso (Adediran et al, 2003;Riedel et al, 2008;Staugaitis et al, 2016). Kompostuojant susidaro ne tik dirvožemiui ir augalams naudingos, bet ir aplinkai pavojingos medžiagos: sunkieji metalai ir patvarūs organiniai junginiai (Cesaro et al, 2015).…”
Section: įVadasunclassified
“…The results showed that highly diluted piggery digestate can be a suitable medium for culturing microalgae, while a high removal efficiency (up to90%) for ammonia, total nitrogen, and phosphate were obtained. Staugaitis et al (2016) investigated the influence of composts on the yield and chemical elements of winter wheat and spring barley. This study indicated that composts processed with no mineral fertilizer did not enhance grain and straw production from winter wheat, but the composts did increase the spring barley grain yield.…”
Section: Ahmadmentioning
confidence: 99%